Desacralization of Acehnese Sultanate Gravestones: Breakdown of Sacred Value Communication - Iskandar; Sri Rochana Widyastutiningrum; Irwan Abdullah; Sumbo Tinarbuko (FAKULTAS DAKWAH UIN SALATIGA, 2026)
The condition of gravestones associated with the Aceh Darussalam and Samudera Pasai Sultanates reflects a transformation in how sacred value is communicated within contemporary social life. Previous studies largely position gravestones as historical artifacts or objects of preservation, leaving a limited explanation of how their meaning is mediated through everyday practice. This study examines how routine interactions function as communicative processes that reshape the transmission of sacred value in postcolonial Aceh. Using a qualitative, practice-oriented approach, data were collected through field observation, in-depth interviews with five institutional and community informants, and document analysis across Aceh Besar, Banda Aceh, and Pidie. Thematic analysis identifies three recurring practices, functional reassignment, spatial neglect, and relocation, through which gravestones are disengaged from their religious and historical meanings. These findings indicate not reinterpretation but a breakdown in communicative transmission, shaped by disrupted historical knowledge, spatial pressure, and institutional limitations. The study reframes desacralization as a problem of mediated meaning and proposes communication-based heritage strategies grounded in historical literacy and situated interpretation.